2011
DOI: 10.3389/fcimb.2011.00015
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cenocepacia differential gene expression during host–pathogen interactions and adaptation to the host environment

Abstract: Members of the Burkholderia cepacia complex (Bcc) are important in medical, biotechnological, and agricultural disciplines. These bacteria naturally occur in soil and water environments and have adapted to survive in association with plants and animals including humans. All Bcc species are opportunistic pathogens including Burkholderia cenocepacia that causes infections in cystic fibrosis and chronic granulomatous disease patients. The adaptation of B. cenocepacia to the host environment was assessed in a rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 96 publications
2
24
0
Order By: Relevance
“…We have recently shown that attachment to CF epithelial cells was enhanced over time of chronic colonization in a series of sequential clinical B. cenocepacia isolates (Cullen et al, accepted manuscript); therefore, the observed induction of Pal in the chronic rat infection model complements our findings as it suggests that Pal may contribute to the enhanced host cell attachment observed in the clinical chronic infection isolates and its expression may contribute to successful colonization of the host. The involvement in host cell attachment is also consistent with findings that a lipoprotein, which subsequently showed 95.8% identity to the Pal encoded by BCAL3204, was the immunodominant antigen in Bcc infected mice (Makidon et al, ; O'grady & Sokol, ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We have recently shown that attachment to CF epithelial cells was enhanced over time of chronic colonization in a series of sequential clinical B. cenocepacia isolates (Cullen et al, accepted manuscript); therefore, the observed induction of Pal in the chronic rat infection model complements our findings as it suggests that Pal may contribute to the enhanced host cell attachment observed in the clinical chronic infection isolates and its expression may contribute to successful colonization of the host. The involvement in host cell attachment is also consistent with findings that a lipoprotein, which subsequently showed 95.8% identity to the Pal encoded by BCAL3204, was the immunodominant antigen in Bcc infected mice (Makidon et al, ; O'grady & Sokol, ).…”
Section: Discussionsupporting
confidence: 85%
“…Pal was among a group of genes that were induced in vivo in a chronic respiratory infection model, suggesting that it contributed to bacterial adaptation and survival in the lungs (O'grady & Sokol, ). We have recently shown that attachment to CF epithelial cells was enhanced over time of chronic colonization in a series of sequential clinical B. cenocepacia isolates (Cullen et al, accepted manuscript); therefore, the observed induction of Pal in the chronic rat infection model complements our findings as it suggests that Pal may contribute to the enhanced host cell attachment observed in the clinical chronic infection isolates and its expression may contribute to successful colonization of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, homologs of the up-regulated component of the type IVb pilus ( flp subunit) were found to be down-regulated in vivo in a chronic B . cenocepacia infection model in rats [46], suggesting that this pilus is detrimental to in vivo fitness during long-term infections. We also saw that the RNA-binding protein Hfq was upregulated in the fixLJ deletion mutant, suggesting a role for sRNA in modulation of the fix regulon.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in the quantitative PCR results for the QS genes and nonuniformity across the isolates likely reflected a role for QS as a global regulator whose expression is very sensitive to conditions outside the cell (15,18). Nevertheless, the expression of QS genes in isolates from patients A and B matched the microarray data.…”
Section: Resultsmentioning
confidence: 95%